Adaptação transcultural preliminar do Children's Eating Attitude Test (Cheat) para o idioma português The preliminary transcultural adaptation of the Children's Eating Attitude Test (Cheat) for portuguese - Mariana Loureiro Barillari; Paula Costa Teixeira; Norman Hearst; Marcela Salim Kotait; Táki Athanássios Cordas; Maria Aparecida Conti (Revista Brasileira de Saúde Materno Infantil, 2011)
OBJETIVOS: traduzir e adaptar o instrumento "Children's Eating Attitude Test" (Cheat) para o idioma português, avaliar a equivalência semântica e a compreensão verbal. MÉTODOS: envolveu quatro etapas: (1) tradução, (2) retradução, (3) revisão técnica e avaliação semântica, (4) pré-teste - avaliação da compreensão verbal por especialistas em transtorno alimentar. RESULTADOS: as 26 questões foram traduzidas e adaptadas para o idioma português. A versão final constou dos mesmos 26 itens apresentando-se de forma clara e de fácil compreensão (valores médios superior a 4,5 - máximo 5,0). CONCLUSÕES: o instrumento encontra-se traduzido e adaptado para o idioma português demonstrando bons resultados no processo de adaptação transcultural. São necessárias análises de validade externa, equivalência de mensuração e reprodutibilidade. OBJECTIVES: to translate and adapt the "Children's Eating Attitude Test" (Cheat) to Portuguese and evaluate the semantic equivalence and verbal comprehension. METHODS: the process involved four stages: (1) translation, (2) back-translation, (3) technical review and semantic evaluation, (4) pre-test - evaluation of verbal comprehension by specialists in eating disorders. RESULTS: the 26 questions were translated and adapted for Portuguese. The final version contained the same 26 items presented in a clear and easy-tounderstand format (average score higher than 4.5 - maximum 5.0). CONCLUSIONS: the tool has been translated and adapted for Portuguese and the transcultural adaptation process was a success. There is still a need for analyses of external validity, measurement equivalence and reproducibility.